Pathological mechanisms of type 1 diabetes in children: investigation of the exosomal protein expression profile - Bai, Baoling; Gao, Kang; Zhang, Kexin; Liu, Lingyun; Chen, Xiaobo; Zhang, Qin (Frontiers in Endocrinology, 2023)
Type 1 diabetes (T1D) is a serious autoimmune disease with high morbidity and mortality. Early diagnosis and treatment remain unsatisfactory. While the potential for development of T1D biomarkers in circulating exosomes has attracted interest, progress has been limited. This retrospective cohort study investigated the molecular dynamics of plasma exosomal proteins in pediatric T1D patients and potential mechanisms associated with T1D development. Liquid chromatography-tandem mass spectrometry with tandem mass tag (TMT)6 labeling was used to quantify exosomal protein expression profiles in 12 healthy controls and 24 T1D patients stratified by age (≤ 6 years old and > 6 years old) and glycated hemoglobin (HbA1c) levels (> 7% or < 7%). Integrative bioinformatics analyses were validated by western blotting. We identified 1035 differentially expressed proteins (fold change > 1.3) between the T1D patients and healthy controls: 558 in those ≤ 6-year-old and 588 in those > 6-year-old.In those who reached an HbA1c level < 7% following 3 or more months of insulin therapy, the expression levels of most of the altered proteins in both age groups resembled those in healthy controls. Bioinformatics analysis indicated differential expression of exosomal components related to immune functions, hemostasis, cellular stress response, and extracellular matrix organization. Western blotting confirmed alterations in RAB40A, SEMA6D, COL6A5 and TTR proteins. This study characterizing the dynamics in plasma exosomal proteins between two developmental stages of pediatric T1D provides valuable insights into the underlying molecular mechanisms of T1D pathology and suggests potential therapeutic targets for T1D management.